Ankyrin repeat domain-encoding genes in the wPip strain of Wolbachia from the Culex pipiens group - Walker, Thomas (BioMed Central, 2007)
BACKGROUND: Wolbachia are obligate endosymbiotic bacteria maternally transmitted through the egg cytoplasm that are responsible for several reproductive disorders in their insect hosts, such as cytoplasmic incompatibility (CI) in infected mosquitoes. Species in the Culex pipiens complex display an unusually high number of Wolbachia-induced crossing types, and based on present data, only the wPip strain is present. RESULTS: The sequencing of the wPip strain of Wolbachia revealed the presence of 60 ankyrin repeat domain (ANK) encoding genes and expression studies of these genes were carried out in adult mosquitoes. One of these ANK genes, pk2, is shown to be part of an operon of three prophage-associated genes with sex-specific expression, and is present in two identical copies in the genome. Another homolog of pk2 is also present that is differentially expressed in different Cx. pipiens group strains. A further two ANK genes showed sex-specific regulation in wPip-infected Cx. pipiens group adults. CONCLUSION: The high number, variability and differential expression of ANK genes in wPip suggest an important role in Wolbachia biology, and the gene family provides both markers and promising candidates for the study of reproductive manipulation.